Noise Characteristics of semiconductor Laser with Phase- Conjugate Feedback - M.I. Azawe (College of Education for Pure Sciences, 2005)
Noise spectra of semiconductor laser subject to a phase-conjugate feedback were investigated theoretically. Time-delayed rate equations with feedback were solved and characteristic equations for relative intensity noise and frequency noise spectra were derived. Numerical results indicate that the relaxation resonance peak was moved to a new frequency region determined by the amount of feedback, This is a technological importance for the improvement of modulation bandwidth, Noise level was affected by the feedback parameters, mainly; the response time and the feedback rate.